'… A 40-Year-Old Black Man Made the Point to Me': Everyday Knowledge and the Performance of Leadership in Contemporary British Politics. (March 2013) - Atkins, Judi; Finlayson, Alan
In this article we demonstrate the application of rhetorical political analysis in the study of political communication and political ideas and ideologies. Taking the rhetorical use of anecdotes as a case study, we find that their use by mainstream party leaders in Britain has proliferated markedly since the mid-1990s. Drawing on examples from speeches by leaders of all three main parties, we show how these stories are employed as a form of argumentative proof that relies significantly on the elevation of 'everyday' experience and knowledge above expert or technical knowledge. We argue that this reflects a more general 'valorisation of lay knowledge' and, moreover, that it is indicative of a form of populist ideology.